Marketing Chain Analysis Of Big Red Chilli (Capsicum Annum L) In Kedawung District, Sragen Regency - Murtadho, Irfan Rasyid; Mahananto; Prasetyowati, Kusriani (Journal of Rural and Urban Community Studies, 2024)
This study investigates the marketing of large red chilies in Kedawung District, Sragen Regency, Central Java, where farmers often face fluctuating prices, forcing them to sell at the prevailing market rates. Conducted in December 2021, the research focuses on understanding the marketing channels for these chilies amidst unstable prices. Using a descriptive analytical method, the study involved 10 farmers, 10 marketing agencies, and 10 consumers to identify and analyze the marketing channels. The study reveals three main marketing channels with varying structures and margins. Channel I, directly linking farmers to consumers via collectors, has a marketing margin of IDR 2000/Kg and a farmer's share of 88.3%. Channel II, which includes retailers, has a margin of IDR 7000/Kg and a 69% farmer's share. Channel III, involving wholesalers and retailers, shows the highest margin of IDR 9000/Kg with a 62.5% farmer's share. Despite the price fluctuations, all channels are deemed efficient based on the farmer's share data.